Studi Adaptasi Notochelys platynota Jantan dan Betina di Area Konservasi Ex-situ Universitas Bengkulu - Elvida Sari Yunilarosi; Aceng Ruyani; Wiryono Wiryono (PendIPA Journal of Science Education, 2019)
AbstraCT[Adaptation Study of Male and Female Notochelys Platynota in Ex-situ Conservation Area University of Bengkulu]. The purposes of this research were to compare the growth of male N. platynota and female N. platynota, and to know the condition of abiotic factors in ex-situ conservation area at the University of Bengkulu. Nine N. platynotas consisting of four males and five females were kept individually in three cages, each of which consisting of three spaces. Cages were placed at three different spots in the ex-situ conservation area of Bengkulu University. N. platynota was fed with water spinach (Ipomea aquatica) as much as 10% of their body weight, every two days. Data collection was done once a week for five weeks. The data were analyzed to determine: a) weight growth, b) body-thick growth, c) growth of carapace length, d) growth of carapace width, e) growth of plastron length, f) growth of plastron width, and g) environmental factors (air temperature, soil temperature, water pH, soil pH, and humidity. The results showed that: a) N. platynota males experienced a growth of 5.04% higher than the female N. platynota, i.e.only 2.26%, b) the abiotic factor conditions of habitat of N. platynota were the followings: air temperature 30.8ºC, ground temperature 31.8ºC, soil pH 5.1, water pH 7.5 and relative humidity 71.2%. Based on the data of N. platynota growth and abiotic factor condition, it can be concluded that the ex-situ conservation area of Bengkulu University is suitable to be the new habitat for N. platynota. Keywords: Adaptation; ex-situ conservation; growth; notochelys platynota.(Received August 13, 2018; Accepted January 8, 2019; Published February 25, 2019) ABSTRAKPenelitian ini bertujuan untuk: a) membandingkan pertumbuhan Notochelys platynota jantan dan N. platynota betina, (b) mengetahui kondisi faktor abiotik di area konservasi ex-situ Universitas Bengkulu. Sembilan ekor N. platynota yang terdiri dari empat ekor jantan dan lima ekor betina dipelihara secara individu dalam tiga keramba yang terdiri atas tiga plot pada masing-masing keramba.  Keramba di letakkan pada tiga titik berbeda di area konservasi ex-situ Universitas Bengkulu. N. platynota diberi pakan berupa  Kangkung (Ipomea aquatiqa) sebanyak 10% dari berat badan, pemberian pakan dilakukan setiap dua hari sekali. Pengambilan data dilakukan setiap satu kali seminggu selama lima pekan. Data dianalisis untuk mengetahui: (a) pertumbuhan berat badan, (b) pertumbuhan tebal badan, (c) pertumbuhan panjang karapaks, (d) pertumbuhan lebar karapaks, (e) pertumbuhan panjang plastron, (f) pertumbuhan lebar plastron, (g) faktor lingkungan abiotik (suhu air, suhu udara, pH air, pH tanah dan kelembaban udara). Hasil penelitian menunjukkan bahwa: (a) N. platynota jantan mengalami pertumbuhan sebesar 5.04%. lebih tinggi dari pada pertumbuhan N. platynota betina yaitu 2.26% (b) Kondisi faktor abiotik yang menjadi habitat N. platynota antara lain dengan rata-rata: suhu udara 30.8ºC, suhu tanah 31.8ºC, pH tanah 5.1, pH air 7.5 dan kelembaban udara 71.2%. Berdasarkan data hasil pengamatan pertumbuhan N. platynota dan kondisi faktor abiotiknya, dapat di katakan bahwa area konservasi ex-situ Universitas Bengkulu sudah cocok untuk dijadikan habitat baru bagi N. platynota. Kata Kunci: Adaptasi; konservasi ex situ; pertumbuhan; Notochelys platynota.